Gestational weight gain patterns as predictors of cesarean deliveries in women diagnosed with gestational diabetes mellitus - Tzu-Ling Chen; Su-Fen Cheng; Chien-Lin Kuo; Chu-Yu Huang; Chia-Hsun Wu (BMC Pregnancy and Childbirth)
Abstract Background Obesity and excessive gestational weight gain (GWG) have been linked to an increased risk of cesarean section. However, existing literature primarily focuses on weight gain during individual trimesters, lacking a comprehensive assessment of GWG trajectories across all three trimesters. This study aimed to investigate the impact of pre-pregnancy BMI and changes in GWG trajectories from the first to the third trimester on cesarean section in women with confirmed gestational diabetes mellitus (GDM). Methods This retrospective cohort study enrolled 947 women with GDM who delivered between January 2012 and July 2022 in northern Taiwan. GDM was diagnosed by oral glucose tolerance test (OGTT) during 24–28 weeks of gestation. Body mass index cut-offs were based on Asian-specific guidelines. The weekly GWG rate was based on baseline weight and weight at two follow-up measurements. GWG patterns were identified using group-based trajectory modeling analysis (GBTM). Results Gestational weight gain patterns were classified into two groups during the pregnancy period: group 1 (non-rapid excessive weight gain) and group 2 (rapid excessive weight gain), comprising 70.2% and 29.8% of participants, respectively. Our study found that being pre-pregnancy underweight and experiencing rapid excessive weight gain contributed to cesarean section. Binary logistic regression analysis revealed that pre-pregnancy normal body mass index (OR = 2.06; 95% CI: 1.08–3.92) and being overweight/obese (OR = 4.04; 95%CI: 2.12–7.70) were associated with the incidence of cesarean sections. Multiparous women and women with a trajectory of rapid excessive weight gain were more likely to undergo cesarean sections. Conclusions Healthcare professionals should provide education on weight management from pre-pregnancy to pregnancy to reduce the incidence of cesarean sections. Particular attention should be paid to women with gestational diabetes mellitus (GDM) who exhibit rapid excessive weight gain to minimize the risk of cesarean delivery.